Ankle joint position sense acuity differences among stroke survivors at three walking ability levels: a cross-sectional study - Jinyao Xu; Jeremy Witchalls; Elisabeth Preston; Li Pan; Gengyuan Zhang; Gordon Waddington; Roger David Adams; Jia Han (Frontiers in Neurology)
BackgroundDespite the importance of lower limb sensation in walking highlighted in systematic reviews, there is limited research investigating the effect of proprioceptive deficits after stroke and any relationship with walking ability.ObjectivesWith stroke survivors of different walking ability, this study aimed to (1) explore side (affected/unaffected) and movement direction (inversion/plantar flexion) effects in ankle joint position sense (JPS) acuity, and (2) compare ankle JPS acuity between groups of stroke survivors with different walking ability.MethodsSeventy subacute stroke survivors were recruited and divided into three groups based on walking ability, as determined by their gait speed on the 10-Meter Walking Test: household (<0.4 m/s), limited community (0.4–0.8 m/s) and community (>0.8 m/s). Ankle JPS acuity was measured by the active movement extent discrimination apparatus (AMEDA).ResultsA significant difference was found between sides, with the AMEDA scores for the unaffected side significantly higher than for the affected side (F1.67 = 22.508, p < 0.001). The mean AMEDA scores for plantar flexion were significantly higher than for inversion (F1.67 = 21.366, p < 0.001). There was a significant linear increase in ankle JPS acuity with increasing walking ability among stroke survivors (F1.67 = 17.802, p < 0.001).ConclusionAfter stroke, ankle JPS acuity on the affected side was lower than the unaffected side. Stroke survivors had higher ankle JPS acuity in plantar-flexion movements, compared with inversion movements. Overall, stroke survivors with higher ankle JPS acuity tended to have higher walking ability, highlighting the importance of ankle JPS acuity in walking ability after stroke. These findings provide new insights into proprioceptive deficits after stroke and their relevance in neurorehabilitation.